Pengaruh Perilaku Konsumen Terhadap Keputusan Pembelian Fashion Muslimah - Dari, Riri Wulan; Fitri, Atiyah (Journal of Islamic Economics, Banking, and Social Finance, 2025)
The Influence of Consumer Behavior on Muslimah Fashion Purchasing Decisions (Case Study of Muslim Women in Jabodetabek), Sharia Banking Study Program, SEBI School of Islamic Economics, 2024. This research aims to analyze the influence of Muslim consumer behavior on purchasing decisions. The research method used is a quantitative method. This research was conducted in Jabodetabek, namely Gen Z and Millennial Muslim female consumers. The population in this study were Muslim women throughout Jabodetabek with a sample of 100 respondents. The data analysis technique in this research uses Partial Least Square (PLS) and Hypothesis Testing. Data processing in this research uses the SmartPLS 3.0 software program. Based on the research result, it shows that the independent variable (X) of Muslim women’s consumer bihavior significantly influencer the dependent variable (Y) on Muslim women’s fashion purchasing decisions in Jabodetabek. In this study, it can be concluded that the Consumer Behavior variable has a significant effect on Purchasing Decisions, because there are personal factors, psychological factors, and social factors that can influence purchasing decisions on Muslimah fashion. And it can be concluded that the factor that has the most significant effect on purchasing decisions on Muslimah fashion is personal factors.